Evaluation On The Use Of Complementary And Alternative Medicine Among Hypertensive Patients In Baghdad, Iraq: A Mixed Methods Approach - Ibrahim, Inas Rifaat (2018)
The growing interest with complementary and alternative medicine (CAM) is evident among patients with hypertension (HTN). This study aimed to investigate the use and seeking behavior of CAM by hypertensive patients; attitudes towards CAM and towards disclosing it to the doctors before and after an education program; the effect of hypertension-related knowledge (HTN-RK) and health-related quality of life (HRQoL) on patients’ use of CAM. A mixed methodological technique was adopted. The first was a qualitative technique through interviews with 20 patients using semi-structured interview guide. A purposive sampling method was used for patient’s recruitment. The second was a quantitative design where a cross-sectional study was conducted at two major teaching hospitals in Baghdad. A convenience sampling method was used to recruit 400 patients and a validated questionnaire was used for gathering of data. Further, an educative program about CAM was implemented. Results of the qualitative phase detected that 14 patients were using CAM to control the blood pressure. Three major themes were identified familiarity with CAM; perceived benefits; and communication with the physicians. This practice was supportive to the pharmacological treatment and underpinned by the social effect, low cost treatment; religious effects, and cultural perspectives. The quantitative analysis showed that 65.5% of respondents used CAM in the management of HTN.